Novel β‐Glucocerebrosidase Activators That Bind to a New Pocket at a Dimer Interface and Induce Dimerization. Issue 10 (19th January 2021) - Benz, Joerg; Rufer, Arne C.; Huber, Sylwia; Ehler, Andreas; Hug, Melanie; Topp, Andreas; Guba, Wolfgang; Hofmann, Eva Carolina; Jagasia, Ravi; Rodríguez Sarmiento, Rosa María
Abstract: Genetic, preclinical and clinical data link Parkinson's disease and Gaucher's disease and provide a rational entry point to disease modification therapy via enhancement of β‐Glucocerebrosidase (GCase) activity. We discovered a new class of pyrrolo[2, 3‐b]pyrazine activators effecting both Vmax and Km. They bind to human GCase and increase substrate metabolism in the lysosome in a cellular assay. We obtained the first crystal structure for an activator and identified a novel non‐inhibitory binding mode at the interface of a dimer, rationalizing the observed structure–activity relationship (SAR). The compound binds GCase inducing formation of a dimeric state at both endoplasmic reticulum (ER) and lysosomal pHs, as confirmed by analytical ultracentrifugation. Importantly, the pyrrolo[2, 3‐b]pyrazines have central nervous system (CNS) drug‐like properties. Our findings are important for future drug discovery efforts in the field of GCase activation and provide a deeper mechanistic understanding of the requirements for enzymatic activation, pointing to the relevance of dimerization. Abstract : A first crystal structure for a novel GCase activator is obtained and a novel non‐inhibitory binding mode at a dimer interface, rationalizing the observed structure–activity relationship, is identified. Mechanistic insights and key information for future drug discovery efforts towards GCase activation are provided.